Peningkatan Kinerja Taman Pendidikan Al-Quran Bina Qurani Dalam Pengelolaan Administrasi Akademik - Ade Chandra Kusuma; Ningrum Astriawati; Yudhanita Pertiwi; Yudhi Setiyantara (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The purpose of this service is as an effort to improve the performance of the Bina Qurani Al-Qurani Education Center in the management of academic administration related to the management of TPA learning in terms of learning administration management in the form of a Learning Implementation Plan, in addition to providing insight into making administration in TPA learning. The method used in this Service is by training with lectures, questions and answers and mentoring. Data collection techniques were obtained by direct observation, interviews and documentation at the Bina Qurani landfill organization which is located in the hamlet of Jetis Sinduadi Mlati Sleman Yogyakarta. The results of this service resulted in an increase in the performance of the Bina Qurani Landfill by producing a Learning Implementation Plan which was used as a guide in providing Iqra and Quran learning by ustazah or Bina Qurani landfill teachers.